Facebook Social Use and Anxiety: A Replication Attempt - Elizabeth Sillence; Tamsin K Saxton; Thomas Pollet (Human Communication & Technology, 2021)
The relationship between social media use and mental health remains under scrutiny by researchers, policy makers, and the general public. Recently, researchers have addressed whether Facebook use is beneficial to people with high social anxiety. The findings from such studies are mixed, partly due to differences in how variables are operationalised. A study by McCord et al (McCord, B., Rodebaugh, T. L., & Levinson, C. A., 2014. Facebook: Social uses and anxiety.  Computers in Human Behavior, 34, 23-27) suggested that the inclusion of a new variable, Facebook-centric social anxiety, helps explain the complex relationship between general social anxiety and frequency of usage of socially-interactive Facebook features. We undertook two studies (N=202 and N=542; majority British and non-student participants) with the aim of replicating McCord et al (2014), using the original measures (general social anxiety, Facebook-centric social anxiety, and frequency of usage of socially-interactive Facebook features). Replicating the original study, we found a significant positive association between general social anxiety and Facebook-centric social anxiety. However, unlike the original study, we did not find evidence that general social anxiety and Facebook-centric social anxiety interacted to predict frequency of usage of socially-interactive Facebook features. We discuss the implications for future research on social Facebook use.